Effects of Self-Myofascial Release Using a Foam Roller on the Stiffness of the Gastrocnemius-Achilles Tendon Complex and Ankle Dorsiflexion Range of Motion - Chang, Tian-Tian; Li, Zhe; Zhu, Yuan-Chun; Wang, Xue-Qiang; Zhang, Zhi-Jie (Frontiers in Physiology, 2021)
Increased muscle stiffness can contribute to reduced range of motion (ROM) and impaired function. Reduced ankle dorsiflexion ROM has been associated with increased injury risk in the ankle. Self-myofascial release has been widely used in clinical and sports settings, but the effects of self-myofascial release on gastrocnemius and Achilles tendon (AT) stiffness are unclear. Therefore, we investigated the effects of self-myofascial release using a foam roller on the stiffness of the gastrocnemius–AT complex and ankle dorsiflexion ROM. Fifty healthy, untrained, and non-sedentary participants (age=22.5±2.6y) were randomly divided into an intervention group (foam roller group) and a control group. The subjects in the intervention group received a single foam roller intervention (3 sets of 1 minute), while the subjects in the control group performed a 5-minute sedentary rest. Stiffness of the gastrocnemius–AT complex was evaluated using MyotonPRO and the ankle dorsiflexion ROM was assessed using the weight-bearing lunge test. For the foam roller and control groups, the between-group analysis revealed a statistically significant difference in gastrocnemius stiffness and ankle dorsiflexion ROM after intervention (P<0.05). Within-group analysis revealed a significant increase in ROM and a significant decrease in medial and lateral gastrocnemius stiffness for the foam roller group after the intervention (P<0.05). In addition, further analysis of the preintervention data revealed a significant negative correlation between ankle dorsiflexion ROM and AT stiffness (r= -0.378 and P= 0.007). These results suggest that self-myofascial release using a foam roller on the calf is an effective method for decreasing the stiffness of the gastrocnemius and increasing ankle dorsiflexion ROM.